Pengaruh model Pembelajaran Kooperatif Tipe TGT berbantuan Media quizizz terhadap hasil belajar IPA Siswa Kelas VI - Ridha, Muhammad Paqih; Sulistyowati, Sulistyowati; Utama Rizal, Setria (Lembaga Dongan Dosen, 2025)
Abstract− Many science learning materials are contextual, because they are related to natural phenomena and everyday life. However, these concepts are often abstract and require deep understanding, and often involve complex processes and theories that result in boredom if only delivered using the lecture method, therefore an effective and efficient learning model is needed. This study aims to describe 1. the application of the TGT (Teams Games Tournament) cooperative learning model assisted by Quizizz media to improve student learning outcomes in science lessons for grade VI at MIS Hidayatul Muhajirin Palangka Raya. 2. the effect of the TGT (Teams Games Tournament) cooperative learning model assisted by Quizizz media to improve student learning outcomes in science lessons for grade VI at MIS Hidayatul Muhajirin Palangka Raya. The research method used in this study is quantitative with a One-Group Pretest-Posttest design. Data collection techniques include learning outcome tests (pretest and posttest), as well as student observation during the learning process. 1. The results of the study showed that the implementation of this learning model went very well, with a total observation value reaching 91. With the implementation that went very well, it also had an impact on the results of the study showing that there was a significant difference between the students' pretest and posttest scores. 2. The students' pretest scores were obtained on average at 56.81, while the average posttest score increased to 85.36. The results of the statistical analysis with the paired sample t-test showed a significance value of 0.000, which was smaller than the significance level (a) of 0.05, so H0 was rejected and there was a significant difference between learning outcomes before and after treatment. The t-count value was -8.853. This shows that there is a significant difference between learning outcomes before and after treatment with a moderate category. Thus, the applied learning model has proven to be effective in improving student learning outcomes in animal reproduction material for grade VI.